Keefektifan Penggunaan Laboratorium IPA di SMP Negeri 1 Sambi Boyolali ditinjau dari Kelengkapan Sarana Prasarana, Kemampuan Guru, dan Teknis Pengelolaan Laboratorium - Abdullah, Zaid Wisnu, Dr. Sofyan Anif, M.Si (2015)
Laboratory is a place of learning through practical methods that can produce a learning experience where students interact with a variety of tools and materials to observe phenomena that can be observed directly and prove myself something learned. Teaching that only based only on theory without practice in learning science is not effective. Effective laboratory management determine the size of the laboratory's contribution in the process of learning science. This study aims to determine the effectiveness of the use of science laboratories in State Junior High School of Sambi 1 Boyolali in terms of completeness of laboratory infrastructure, the ability of teachers, and laboratory management technical. This research is a qualitative descriptive study using a case study approach, data collection techniques done with the study questionnaires, interviews and documentation. Data obtained in the form of assessment instruments are drawn from the results of questionnaires grade science teacher VII and VIII. The data has been analyzed using descriptive statistics. Based on the results of the study show that the effectiveness of the use of science laboratories are effective (90.09%). This is evident from the average of three factors: completeness of laboratory infrastructures (98.15%), the ability of teachers (80.83%), and technical laboratory management (91.30%). At the completion of laboratory infrastructure has been standardized in Permendiknas 24 of 2007 the minimum threshold that must be met in laboratory research results still approaching means complete (98.15%). The ability of teachers and technical management of the laboratory showed very good category. It can be concluded that the effectiveness of the use of science laboratories in State Junior High School of Sambi 1 Boyolali in terms of completeness of laboratory infrastructure, the ability of teachers, and technical management of the laboratory has been said to be effective.